Heavy Metal Accumulation at the Bertam Agricultural Watershed in Cameron Highlands, Malaysia - S.H, Haron; S, Ismail; L.M, Sidek (International Journal of Engineering and Technology, 2018)
The existence of heavy metals residues in water, soil and air poses a serious risk to all living organisms. Heavy metals, such as Cd, Pb, Cr, Ni, and Hg, are major sources of environmental pollution, especially in areas with high anthropogenic and agriculture activities. The objective of this study is to determine the status of heavy metal concentrations of Cd, Cr, Ni, Pb, Zn, Cu, and Fe in the water bodies of Bertam River, which passes through agricultural areas. The water samples were collected randomly in three replicates from 10 sampling points along the Bertam River. The heavy metals in the water were extracted by using filter paper with a pore size of 0.45 mm. The extracted water sample was preserved by adding nitric acid (pH <2). Sample concentrations were then tested for metal concentrations using inductively coupled plasma mass spectrometry. In this study, the highest mean concentration was Fe (96.04 ± 90.43 ppb), followed by Zn (5.68 ± 0.2.34 ppb), Cu (5.13 ± 2.98 ppb), Cr (1.53 ± 0.19 ppb), Ni (0.85 ± 0.22 ppb), Pb (0.85 ± 1.61 ppb), and Cd (0.027 ± 0.02 ppb), where Fe> Zn> Cu> Pb> Cr> Ni> Cd. However, the concentrations of selected heavy metals in the water samples were below the standards recommended by the World Health Organization.